Polycentric urban form and non-work travel in Singapore: A focus on seniors. (August 2019) - Hou, Yuting
Highlights: Better access to the CBD decreases walking trips for most of age groups. Impacts of access to lower-tiers of centers on walking trips vary among older adults. High density and good street connectivity encourage walking trips for all adults. Abstract: This study explores how the planned polycentric urban form in Singapore influences local residents' non-work trip frequency of different transport modes and how the travel impacts of access to the planned commercial/activity centers vary between the non-elderly adults (aged 20–54) and older adults (aged 55 and over) of different subgroups. The study applies a categorical variable approach to account for independent effects of aging and its interaction effects with urban form variables while controlling for neighborhood-scale land use characteristics. The results indicate that better access to different tiers of planned urban centers is associated with more walking trips for some age groups of older people but less walking trips for other age groups. Neighborhood-level land use characteristics such as higher density and better street connectivity significantly increase walking trips for all adults with no differential effects across age. This study provides new empirical evidence on the differential travel impacts of urban form between younger adults and older adults of different subgroups. The findings also provide some insights on evaluating the performance of polycentric urban development strategy and land use policies of Singapore in terms of facilitating local residents' daily mobility.